Forest structure and composition alleviate human thermal stress - Gillerot, Loïc; Landuyt, Dries; Oh, Rachel; Chow, Winston; Haluza, Daniela; Ponette, Quentin; Jactel, Hervé; Bruelheide, Helge; Jaroszewicz, Bogdan; Scherer‐Lorenzen, Michael; De Frenne, Pieter; Muys, Bart; et al. (Global change biology, 2022)
Current climate change aggravates human health hazards posed by heat stress. Forests can locally mitigate this by acting as strong thermal buffers, yet potential mediation by forest ecological characteristics remains underexplored. We report over 14 months of hourly microclimate data from 131 forest plots across four European countries and compare these to open‐field controls using physiologically equivalent temperature (PET) to reflect human thermal perception. Forests slightly tempered cold extremes, but the strongest buffering occurred under very hot conditions (PET >35°C), where forests reduced strong to extreme heat stress day occurrence by 84.1%. Mature forests cooled the microclimate by 12.1 to 14.5°C PET under, respectively, strong and extreme heat stress conditions. Even young plantations reduced those conditions by 10°C PET. Forest structure strongly modulated the buffering capacity, which was enhanced by increasing stand density, canopy height and canopy closure. Tree species composition had a more modest yet significant influence: that is, strongly shade‐casting, small‐leaved evergreen species amplified cooling. Tree diversity had little direct influences, though indirect effects through stand structure remain possible. Forests in general, both young and mature, are thus strong thermal stress reducers, but their cooling potential can be even further amplified, given targeted (urban) forest management that considers these new insights. Young forest plantations but especially mature stands have a cooling capacity that strongly increases the hotter it becomes, with forest microclimates getting well over 10°C cooler when temperatures become a potential health hazard for humans. Yet, targeted forest management can even further enhance this heat stress mitigation by adapting stand structure in the first place, and tweaking the species composition in the second place. The tree diversity seems of little direct importance, although it likely has beneficial long‐term effects that were not studied here.